Solve the system of equations using substitution. Since both equations are already in the "y=" form, we can set x2+3 equal to -x2+5:
x2 + 3 = -x2 + 5
Rearrange the terms:
2x2 = 2
Solving, we get that x = 1 or x = -1. But we are not done yet! Solving the system means getting x and y values.
We can plug the values we found for x into either of the original equations. I recommend trying both equations just to make sure that your answers do work in both.
We get y=4 for both x=1 and x=-1 in both equations. So
the solution is (1,4) and (-1,4).
Hope this helps!